Child outcomes after amnioinfusion compared with no intervention in women with second‐trimester rupture of membranes: a long‐term follow‐up study of the PROMEXIL‐III trial. (4th March 2020) - de Ruigh, AA; Simons, NE; van 't Hooft, J; van Teeffelen, AS; Duijnhoven, RG; van Wassenaer‐Leemhuis, AG; Aarnoudse‐Moens, C; van de Beek, C; Oepkes, D; Haak, MC; Woiski, M; Porath, MM; et al.
Abstract : Objective: To assess the effect of transabdominal amnioinfusion or no intervention on long‐term outcomes in children born after second‐trimester prelabour rupture of the membranes (PROM between 16 +0/7 –24 +0/7  weeks) and oligohydramnios. Population: Follow up of infants of women who participated in the randomised controlled trial: PPROMEXIL‐III (NTR3492). Methods: Surviving infants were invited for neurodevelopmental assessment up to 5 years of corrected age using a Bayley Scales of Infant and Toddler Development or a Wechsler Preschool and Primary Scale of Intelligence. Parents were asked to complete several questionnaires. Main outcome measures: Neurodevelopmental outcomes were measured. Mild delay was defined as −1 standard deviation (SD), severe delay as −2 SD. Healthy long‐term survival was defined as survival without neurodevelopmental delay or respiratory problems. Results: In the amnioinfusion group, 18/28 children (64%) died versus 21/28 (75%) in the no intervention group (relative risk 0.86; 95% confidence interval [CI] 0.60–1.22). Follow‐up data were obtained from 14/17 (82%) children (10 amnioinfusion, 4 no intervention). In both groups, 2/28 (7.1%) had a mild neurodevelopmental delay. No severe delay was seen. Healthy long‐term survival occurred in 5/28 children (17.9%) after amnioinfusion versus 2/28 (7.1%) after no intervention (odds ratio 2.50; 95% CI 0.53–11.83). When analysing data for all assessed survivors, 10/14 (71.4%) survived without mild neurodevelopmental delay and 7/14 (50%) were classified healthy long‐term survivor. Conclusions: In this small sample of women suffering second‐trimester PROM and oligohydramnios, amnioinfusion did not improve long‐term outcomes. Overall, 71% of survivors had no neurodevelopmental delay. Tweetable abstract: Healthy long‐term survival was comparable for children born after second‐trimester PROM and treatment with amnioinfusion or no intervention. Tweetable abstract: Healthy long‐term survival was comparable for children born after second‐trimester PROM and treatment with amnioinfusion or no intervention.